THE INFLUENCE OF PERFORMANCE EXPECTATIONS, BUSINESS EXPECTATIONS, SOCIAL INFLUENCE, AND CONDITIONS THAT FACILITATE PAYMENT INTEREST NON-CASH - Faza Hakimul Adli; Sambas Ade Kesuma; Risanty Risanty; Taufik Akbar Parluhutan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to find out and analyze the influence of performance expectations, business expectations, social influences, and facilitating conditions on the interest in non-cash payments both partially and simultaneously in students of Universitas Muslim Nusantara Al-Washliyah. The population in this study includes 4554 active students for the 2025/2026 academic year at the Muslim University of Nusantara Al Washliyah and a research sample of 445 respondents. In this study, data was collected through questionnaires. The results of the study show that performance expectations, business expectations, social influences and facilitating conditions have a significant positive effect on the interest in partial non-cash payments. Simultaneously, performance expectations, business expectations, social influences and facilitating conditions affect the interest in non-cash payments in students of Universitas Muslim Nusantara Al-Washliyah